A NEEDS ANALYSIS FOR ESP IN A MULTIMEDIA STUDY PROGRAMME OF A VOCATIONAL HIGH SCHOOL - Santika, Susan; Wirza, Yanty; Emilia, Emi (International Journal of Education, 2022)
A needs analysis is required to design ESP courses and determine appropriate materials for vocational high school students. Particularly in a multimedia study programme, even while multimedia has become increasingly prominent as a result of digital transformations, there is not much attention given to conducting the need analysis for vocational high school students. Therefore, this research aims to analyze the needs analysis for ESP in a multimedia study programme of a vocational high school. Specifically, it attempts to reveal what difficulties are encountered by the students during their internship programmes, what English language skills are needed by the students to perform their jobs, and what the multimedia study programme needs to offer to allow students’ employability. A case study was conducted on an EFL teacher and eighteen students in a vocational high school. The findings revealed that: First, students had difficulties in Grammar, Vocabulary, and Speaking; Second, the English language skills needed to perform their jobs were listening, reading, and writing; Third, the multimedia study programme should offer copywriting, technical vocabulary and authentic materials related to multimedia to allow students’ employability. This research also recommends three-unit materials for the ESP courses divided into three topics: copywriting, photography, and videography.